A new classification of rosette-forming Brachyglottis (Asteraceae: Senecioneae) recognising a single species: Brachyglottis lagopus. Issue 3 (3rd July 2018) - Millar, Timothy R.; Breitwieser, Ilse; Pelser, Pieter B.; Smissen, Rob D.
ABSTRACT: The rosette-forming group of Brachyglottis (Asteraceae: Senecioneae) is a New Zealand endemic species complex in which five species are currently recognised. Although there are clear morphological differences between some members of this group (for example, in trichome characters), morphological intermediates and sites where plants display considerable variation in diagnostic characters are common. Using existing keys and descriptions many specimens of this group can therefore not be identified to species with confidence. In this study, analyses of morphological, DNA sequence and simple sequence repeat data are used to test the existing delimitation, with the intention of revising the taxonomic treatment of the group. Our results show that variation in morphological characters in the rosette Brachyglottis group is continuous, making species delimitation arbitrary. Moreover, they demonstrate that the current species classification does not reflect genetic relationships in the group. Instead, there is a strong geographical pattern in the genetic data which we attribute to isolation by distance. Our findings are consistent with a single but morphologically variable species within which infraspecific taxa cannot be unambiguously recognised. We therefore recognise a single broadly circumscribed rosette-forming Brachyglottis species, Brachyglottis lagopus, and provide a full synonymy.